Personality disorders as predictors of intimate partner violence: A meta-analysis. (August 2021) - Collison, Katherine L.; Lynam, Donald R.
Abstract: Despite years of research demonstrating a relation between personality pathology and intimate partner violence (IPV), no meta-analysis has been published examining how well, or poorly, all ten personality disorders (PDs) predict IPV perpetration or victimization, nor has any meta-analysis examined these relations across types of IPV. Therefore, the present study was undertaken to synthesize existing research on the effects of all ten PDs, as well as psychopathy and global PD symptoms, on physical, psychological, and sexual IPV perpetration and victimization. An initial search in PsycINFO, PubMed, and Sociological Abstracts yielded 3988 results. After duplicate and irrelevant articles were removed, 163 studies were included in the analysis, representing 189 individual samples. Analysis was conducted in R using the metafor package. Main effects analyses indicate that PDs were significantly and positively related to IPV perpetration. Results were more mixed for IPV victimization. Antisocial and borderline PDs demonstrated the most robust effect sizes across both perpetration and victimization. Moderator analyses suggested that with few exceptions, main effects were consistent across a number of sample and study characteristics. Findings may help to inform prevention and intervention efforts in clinical settings. Highlights: Most personality disorders were significantly related to IPV perpetration. With the exception of NPD, results were generally similar for IPV victimization. Antisocial and borderline PDs demonstrated the most robust effect sizes. The results did not vary substantially across types of IPV. Study characteristics did not generally moderate these effects.